GLTSCR1 Negatively Regulates BRD4‐Dependent Transcription Elongation and Inhibits CRC Metastasis. Issue 23 (16th October 2019) - Han, Fengyan; Zhang, Lei; Chen, Chaoyi; Wang, Yan; Zhang, Yi; Qian, Lili; Sun, Wenjie; Zhou, Dan; Yang, Beibei; Zhang, Honghe; Lai, Maode
Abstract: Frameshift mutations frequently occur in colorectal cancer (CRC) with microsatellite instability (MSI), but the nature and biological function of many MSI‐associated mutations remain elusive. Here, an MSI frameshift mutation is identified in glioma tumor suppressor candidate region gene 1 ( GLTSCR1 ) that produces two C‐terminal‐truncated proteins. Additionally, GLTSCR1 is verified as a tumor suppressor that inhibits CRC metastasis. Through binding to bromodomains and the phosphorylation‐dependent interaction domain of bromodomain protein 4 (BRD4) via the C‐terminus, GLTSCR1 blocks oncogenic transcriptional elongation. However, truncated GLTSCR1 translocates into the cytoplasm and loses BRD4 binding domain, which induces the phosphorylation of RNA Pol II at Ser2 and dephosphorylation at Ser5, then increases oncogenic transcriptional elongation. Importantly, GLTSCR1 deficiency decreases sensitivity to bromodomain and extra terminal domain inhibitors. This study highlights the molecular mechanism of the GLTSCR1‐BRD4 interaction, which is a potential therapeutic target for CRC. Abstract : This study reports a microsatellite instability‐selected frameshift mutation in glioma tumor suppressor candidate region gene 1 ( GLTSCR1 ) that converts GLTSCR1 from an antimetastatic gene to a prometastatic gene. A bromodomain protein 4‐GLTSCR1‐DNA model is proposed in which the truncated GLTSCR1 coregulates the oncogenic transcriptional elongation and these findings provide a strong rationale for targeting GLTSCR1 in colorectal cancer.